Efeitos da fisioterapia nos programas de atenção no processo de envelhecimento sobre qualidade de vida e parâmetros físicos - Castro, Paula Costa (Universidade Federal de São Carlos, 2011)
Different programs adapted to the elderly have been proposed in order to assist and promote healthy aging, including physical therapy interventions. The effects of these programs on the participants quality of life and physical parameters are often unknown, and require investigation. This study s purpose was to develop a physical therapy collective intervention and understand how the programs São Carlos Senior University and the Geriatric Revitalizations influence quality of life, strength, flexibility, dynamic balance and physical conditioning of the participants. As a result of this study, four papers were produced. Paper one discusses the physical therapist participation at Senior Universities for physical training in a community-based program. It also describes an intervention group therapy as a part of an interdisciplinary program at São Carlos Senior University. The second paper compares the psychometric properties and correlations of two quality of life instruments, the Medical Outcomes Study 36 Item Short-Form health survey (SF-36) and The World Health Organization Quality of Life (WHOQOL)-BREF, in a sample of Brazilian elderly. Both scales showed acceptable reliability, but a poor correlation was observed between the two questionnaires related fields. The WHOQOL-BREF seems to be a better choice for an overall assessment of quality of life and the SF-36 can better discriminate between health-related known groups. The third paper presents the influence on quality of life of middle-aged and elderly post 10-month intervention at São Carlos Senior University and Geriatric Revitalization Program. UATI Group showed significant increase in quality of life level according to the overall WHOQOL bref score; REVT Group showed significant increase in health related domains. Both groups showed improvement when compared to the Control Group. The forth paper presents a 6-month, 1, 2 and three-year follow-up of Senior University and Geriatric Revitalization in the physical variables of the participants. REVT Group showed better results than UATI Group. Both intervention-groups showed better results than Control Group. These community-based programs contributed to strength, flexibility, dynamic balance and physical conditioning improvement or maintenance. Despite the differences, both programs improved quality of life and physical parameters in the participants. Senior University and Geriatric Revitalization can be considered valid choices as assistance programs in the aging process.
Keywords: Gerontologia; Revitalização geriátrica; Universidade da terceira idade; WHOQOLBREF; Capacidade funcional; Idoso; Universidade sênior; SF-36; Força muscular de preensão palmar; Flexibilidade; Condicionamento físico; Controle postural; Eldely; Senior university; Geriatric revitalization; Physical therapy; WHOQOL BREF; SF-36; Manual pressing strength; Flexibility; Balance; Physical conditioning; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL